Pengaruh Financial Knowledge Dan Internal Locus Of Control Terhadap Financial Management Behaviour Pelaku Industri Keramik Dinoyo Kota Malang - Ramadhona Adi Saputra; Nurhidayah Nurhidayah; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to learn about and examine Dinoyo ceramic industry artisans' financial management practices in Malang City in 2023. Financial Knowledge and Internal Locus of Control are the independent variables influencing this study. The kind of examination utilized is clear with a quantitative methodology, and that implies making sense of the connection between the free factors and the reliant variable. Quantitative The SPSS program is used to conduct multiple linear regression analysis on the data. Through the distribution of questionnaires and direct observation, primary data were obtained directly. As per information from the Executive of the Dinoyo ceramics affiliation, Malang City, in 2023, the populace got was 23 skilled workers. Furthermore. According to the findings of the study, internal locus of control and partially financial knowledge had a positive and significant effect on financial management behavior among Dinoyo ceramic industry craftsmen in Malang City. Behaviors related to financial management were also significantly influenced by financial knowledge among Dinoyo ceramic industry craftsmen in Malang City. Keywords: Financial Management Behavior, Financial Knowledge, Internal Locus of Control, Ceramic Craftsmen